Pengaruh Ketebalan Lapisan Aktif terhadap Karakteristik Sel Surya Berbasis a-Si:H yang Ditumbuhkan dengan Teknik HWC-VHF-PECVD - Ida Usman; Toto Winata (Jurnal Matematika & Sains, 2008)
The HWC-VHF-PECVD (Hot Wire Cell Very High Frequency Plasma Enhanced Chemical Vapor Deposition) technique has been developed for silicon thin film deposition. The developed technique was also used to fabricate the hydrogenated amorphous silicon (a-Si:H) based p-i-n solar cells with varied active layer (i-layer) thickness. Based on the measurement result of current-voltage (I-V) characteristic of resulted solar cells, it is known that the conversion efficiencies are influenced by the i-layer thickness of each solar cell. In this research, the highest conversion efficiency of 9,39 % was achieved from solar cell with i-layer of 5500 Ã thickness. All of solar cell parameters decrease as the ilayer thickness increases to 6000 Ã, which were probably affected by the serial resistance increases that marked by the degradation of fill factor value.